Tobacco and obesity epidemics: not so different after all? - Chopra, Mickey (BMJ Publishing Group Ltd., 2004)
Campaigns to promote healthy eating are undermined by the ubiquity of processed, energy dense foods. A global strategy is now needed to tackle the rising prevalence of obesity